PARTICIPATION IN THE PROCESS OF EUROPEAN INTEGRATIONAS A MEANS OF COOPERATION OF THE HOLY SEEWITH INTERNATIONAL ORGANISATIONS - Wielgosz, Maria Aleksandra (Review of European and Comparative Law, 2020)
A dynamic development of politics and international European relations makes the analysis of them considerably more difficult . Current research and analytical interest in it concentrates on the process of so-called European integra-tion . The European Union is an epitome of a specific vision of humanity and a model of a society having a specific attitude towards certain values, in particular: systems of protecting human rights, respect for religious and cultural differences and dynamic economic development . The Holy See is not only a passive onlooker of civilisation changes . Concern for common welfare and peace keeping between particular nations was, is and always will be its priority . That is why it undertakes various forms of cooperation with international organisations . One of them is an eager interest and participation in European integration processes . The key and universal value connecting international organisations and the Holy See is still an inborn human dignity, which unites integration urge of many nations